DEIXIS IN JOHN GREEN’S NOVEL ENTITLED LOOKING FOR ALASKA - Marlin Hati; Laia, M. Yunus; Telaumbanua, Tatema (Research on English Language Education, 2021)
This thesis studies the use of deixis that occurred in John Green’s novel entitiled Looking for Alaska. The objectives of this research are classifying the types of deixis found in John Green’s novel Looking for Alaska and describing how the deixis use in John Green’s novel Looking for Alaska. In this research, the researcher used the deixis, theory, namely person deixis, temporal deixis, spatial deixis, discourse deixis, and social deixis. This study used qualitative methods with descriptive approach. The data of this research was the utterance or sentence containing deixis that occurred in John Green’s novel Looking for Alaska. In analyzing the data, the researcher used the theory of Levinson. The result of analysis shows that there are five types of deixis in John Green’s novel, they are person deixis, temporal deixis, spatial deixis, discourse deixis, and social deixis. The person deixis found in sentence and utterance in novel Looking for Alaska are I, us, me, you, your, we, my, him, her, she, he, they, them, their, our, herself, myself, himself, themselves, and yourself. The spatial deixis found in the utterance novel Looking for Alaska are here and there. The temporal deixis found in the utterance in novel Looking for Alaska is now, then, last year, that evening, yesterday, today, to night, last night, the afternoon, next morning, next time, tomorrow, last week, and next day”. The discourse deixis found in utterance in novel Looking for Alaska is this, that, these, and those. Then, the social deixis found in utterance in novel Looking for Alaska is American President. the analysis of this research shows that the deixis used in the novel does not have the same reference. It depends on the context and situation of scene in the novel. Therefore, the readers must know the context and the situation of the novel in order to understand the reference of deitic words. Hopefully the findings of this study could be useful in providing understanding on deixis theory.